Colonic content: effect of diet, meals, and defecation. Issue 2 (21st August 2016) - Bendezú, R. A.; Mego, M.; Monclus, E.; Merino, X.; Accarino, A.; Malagelada, J. R.; Navazo, I.; Azpiroz, F.
Abstract: Background: The metabolic activity of colonic microbiota is influenced by diet; however, the relationship between metabolism and colonic content is not known. Our aim was to determine the effect of meals, defecation, and diet on colonic content. Methods: In 10 healthy subjects, two abdominal MRI scans were acquired during fasting, 1 week apart, and after 3 days on low‐ and high‐residue diets, respectively. With each diet, daily fecal output and the number of daytime anal gas evacuations were measured. On the first study day, a second scan was acquired 4 hours after a test meal (n=6) or after 4 hours with nil ingestion (n=4). On the second study day, a scan was also acquired after a spontaneous bowel movement. Results: On the low‐residue diet, daily fecal volume averaged 145 ± 15 mL; subjects passed 10.6 ± 1.6 daytime anal gas evacuations and, by the third day, non‐gaseous colonic content was 479 ± 36 mL. The high‐residue diet increased the three parameters to 16.5 ± 2.9 anal gas evacuations, 223 ± 19 mL fecal output, and 616 ± 55 mL non‐gaseous colonic content ( P <.05 vs low‐residue diet for all). On the low‐residue diet, non‐gaseous content in the right colon had increased by 41 ± 11 mL, 4 hours after the test meal, whereas no significant change was observed after 4‐hour fast (−15 ± 8 mL; P =.006 vs fed). Defecation significantly reduced the non‐gaseous content in distal colonic segments. Conclusion & Inferences: Colonic content exhibits physiologic variations with an approximate 1/3 daily turnover produced by meals and defecation, superimposed over diet‐related day‐to‐day variations. Abstract : Ingestion of unabsorbable residues and defecation produce profound changes in colonic content. The rapid turnover of colonic biomass (about 1/3 daily) indicates a high adaptation potential of microbiota to the intraluminal environment.